Analysis of Bone Destruction Mechanism by Aggregatibacter Actinomycetemcomitans: A Systematic Review - Idrus, Erik; Ardiman, Karenina Raihani Amalia; Lestari, Widya; Mandasari, Masita; Soekanto, Sri Angky (UI Scholars Hub, 2024)
Periodontitis is a disease marked by inflammation of the periodontium, caused by biofilms present in the oral cavity, and results in alveolar bone destruction. One of the main hallmarks of periodontitis is the presence of Aggregatibacter actinomycetecomitans, which is generally suppressed by antibiotic administration. The strategy to control A. actinomycetecomitans by small specific peptide inhibitors potentially halts the progression of alveolar bone damage while lowering the risk of antibiotic resistance. The detailed interaction mechanisms of A. actinomycetecomitans and bone cells are fundamental to discovering and constructing the specific inhibitor. Objective : To systematically review the mechanism of bone destruction by A. actinomycetecomitans based on its interaction with bone cells and its precursors. Methods: A comprehensive search was performed in two database (Scopus, PubMed) from September 2021 to June 2022, according to the Preferred Reporting Items for SystematicvReviews and Meta-Analyses (PRISMA) protocol. The terms used in the search were ”Aggregatibacter actinomycetemcomitans” OR “A. actinomycetemcomitans” AN” bone”OR “bone loss” OR “bone destruction” OR “bone resorption” OR “bone formation” OR “bone remodelling” OR “osteclast” OR “osteoblast” OR “osteocyte”. Only articles in English and research articles published within ten years were included. Results: In total, nine articles discussing alveolar bone destruction were included in the review. Most articles reported the virulence of A. actinomycetecomitans, lipopolysaccharide (LPS), and its target cells, osteoclast progenitors, osteoclasts, and osteoblasts. Conclusion: A. actinomycetecomitans induces alveolar bone destruction via various mechanisms, including osteoblast apoptosis, lowering osteoblast differentiation, increasing osteoclast activity and differentiation, and releasing inflammatory cytokines. The detailed interaction mechanisms between A. actinomycetecomitans and bone cells would provide valuable hints for further investigation toward constructing specific inhibitors to disrupt the interaction between A. actinomycetecomitans and bone cells that eventually protect the alveolar bone destruction.